2022
DOI: 10.3389/fimmu.2022.880196
|View full text |Cite
|
Sign up to set email alerts
|

Human Disseminated Protothecosis: The Skin is the “Window”?

Abstract: Human disseminated protothecosis is a rare infection caused by members of the genus Prototheca, an achlorophyllic algae always associated with debilitated hosts. The presence of non-budding cells and large, spherical cells (sporangia) with endosporulation (morula) in histology is proof of Prototheca infection. Regrettably, due to the lack of specificity of clinical features and low awareness among clinicians, protothecosis is always underestimated and misdiagnosed. The available data on a species-specific anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Todd et al reviewed 211 cases of protothecosis published between 1964 and 2017 and showed that 66 (31.2%) of these cases occurred in patients without any chronic condition or immunosuppression [ 2 ]. Our patient's case corroborates the information that even in immunocompetent individuals with some incidental disease, protothecosis should be considered in the differential diagnosis, especially when there is no clinical improvement through the antifungal drugs that are used for the most frequent mycoses [ 2 , 3 , 6 , 9 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Todd et al reviewed 211 cases of protothecosis published between 1964 and 2017 and showed that 66 (31.2%) of these cases occurred in patients without any chronic condition or immunosuppression [ 2 ]. Our patient's case corroborates the information that even in immunocompetent individuals with some incidental disease, protothecosis should be considered in the differential diagnosis, especially when there is no clinical improvement through the antifungal drugs that are used for the most frequent mycoses [ 2 , 3 , 6 , 9 ].…”
Section: Discussionsupporting
confidence: 84%
“…Protothecosis is a rare condition, but large number of cases have been described in patients with underlying immunosuppression or several underlying diseases. Systemic steroid use, diabetes mellitus, hematological or solid-tissue malignancy and solid-organ transplantation are the main factors related to increased risk of this disease [ 2 , 3 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Todd et al reviewed 211 cases of protothecosis published between 1964 and 2017 and showed that 66 (31.2%) of these cases occurred in patients without any chronic condition or immunosuppression [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We infer that infection of Prototheca wickerhamii may be due to sewage exposure. The diagnosis of Prototheca usually depends on morphological identification of the organisms in wet slide preparations of cultures and/or direct identification in tissue specimens [ 14 ]. Prototheca species reveal yeast-like colonies on Sabouraud dextrose agar but differ from fungi as they lack glucosamine in their cell walls [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic examination of the organism in culture reveals the same structures as those observed in tissue (spherical sporangia containing multiple endospores). Intracellular spores are characteristic for Prototheca species, yet the number and size are influenced by the culture medium and incubation time [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%